Understanding the Mechanisms of Weed Interference with Crops through Photosynthetic and Antioxidative Physiology - Ratnayaka, H. Harish; Molin, William T.; Sterling, Tracy M. (Recent Progress in Plant and Soil Research Vol. 3, 2021)
Background: Crop losses caused by the interference from weeds continue to be a major hindrance to the global efforts for increasing food and fiber production. Although weed interference with crops includes changes to both biotic and abiotic components of the agroecosystem, weed research usually focuses on the crop-weed competition for the limiting resources. Crop-weed competition studies also understandably assess mostly the crop variables that help generate the recommendations for weed management to minimize the crop losses. Therefore, they generally focus on the competition between the crop and weed(s) for resources such as light, water and nutrients and attempt to provide insight into which resource becomes more limited at specific growth phases of the crop in the presence of different densities of the weed(s). However, the use of cultural practices such as optimal crop densities, regular irrigation and recommended fertilizer application alters the competition for those resources in cotton and many other cropping systems in the U.S. or other developed countries. Therefore, it is difficult to apply the knowledge gained from the aforementioned studies directly to these cropping systems. For instance, the assumption that a weed(s) with similar growth habit and morphology to the crop imposes a more severe competition to the crop may not necessarily hold true in such cropping systems. Simultaneous investigations on the major physiological processes such as carbon gain of both weed(s) and the crop under controlled conditions during interference, however, can provide insight into how the weed(s) may interfere with the crop in those cropping systems. The study presented here shows how a weed species in the same family and with similar growth habit as the crop maintains a gas exchange strategy different from the crop providing deeper insight into to mechanism of the crop-weed interference. Using potted experiments under controlled conditions it also attempts to describe how the crop-weed system may respond to a mild, rather than severe, drought and recovery expected between the times of irrigation in a well-managed cropping system. The influence of plant interference and a mild drought on gas exchange and oxidative stress was investigated using potted plants of two cotton species (Gossypium hirsutum L. cv. Delta Pine 5415, and Gossypium barbadense L. cv. Pima S-7) and spurred anoda (Anoda cristata L. Schlecht.) of the Malvaceae. Without interference, cotton and spurred anoda had similar net photosynthesis (Pnet) but different pigment profiles. Stomatal conductance (gs) and transpiration rate (E) were greater in spurred anoda than cotton. Net photosynthesis and biomass in cotton were reduced more by spurred anoda interference than by intraspecific interference. With interference, the xanthophyll cycle conversion state and a-tocopherol levels increased in cotton, but remained unchanged in spurred anoda. Catalase, ascorbate peroxidase (APX) and glutathione reductase (GR) activities were not influenced by plant interference. Without interference, spurred anoda had lower APX, and similar catalase and GR activities compared with cotton. Mild drought increased APX activity more than 40% in cotton, and 26% in spurred anoda. Upon recovery from drought, drought-induced APX activity was still higher in cotton, and GR activity was higher in previously drought-stressed cotton and spurred anoda plants compared with well-watered plants. The greater impact of spurred anoda interference than intraspecific interference on cotton biomass is due mainly to reduced carbon gain in cotton.